ISLAMIC BOARDING SCHOOL STUDENTS’ LEARNING STYLES IN EFL CLASS - Kalsum Kalsum (Jurnal Bahasa Lingua Scientia, 2022)
Abstract: The students sometimes get confused with the English material because their learning style does not match with the presentation of the teacher. the learning styles need be known by teachers involved in teaching and learning process. This research aims to disclose students' needs for learning English based on their learning styles. This research used quantitative research with survey research methods. The research was conducted on second grade students of MA in three Islamic boarding schools in the city of Parepare, South Sulawesi, Indonesia. The instrument in this study is a questionnaire containing the Perceptual Learning Style Preferences Questionnaire consisting of Visual, Auditory. Kinesthetics, Tactile, Group and Individual Styles. This research discloses that students have more kinesthetics, auditory, visual, and group learning styles. It found that students’ learning styles are major in visual, auditory, kinesthetics, and group learning styles. Meanwhile, some of the students in Boarding School of Parepare are minor in tactile and individual learning styles. Therefore, the teacher should make teaching materials based on the learning style of each student.